Faire bifurquer le tourisme hivernal ? Controverses et mobilisations socio-environnementales autour de la transition écologique dans une station alpine (La Clusaz, France) - Mikaël Chambru; Marion Picard (Mondes du Tourisme)
Based on the case of the project to create a high-altitude reservoir at La Clusaz ski resort in France, this article analyses the opposing appropriations of the so-called ecological transition in the mountains. It shows how the transition becomes a public controversy when social, environmental, political, and technical issues intertwine. By following the history of this mountain controversy, we aim to show how the ecological transition became a public concern around key issues, and how socio-ecological movements participate in this diffusion. Beyond the apparent homogeneity of the ecological transition, Alpine controversies on tourism crystalise antagonistic worldviews, stimulate the development of strategies and stakeholder interactions, and question the transformative dimensions and the aims of the ecological transition. Overall, the article provides an examination of the myriad transitional paths of mountain tourism.